Comparative effectiveness of treatment options for displaced midshaft clavicle fractures. (2021) - Martin, J. R.; Saunders, P. E.; Phillips, M.; Mitchell, S. M.; Mckee, M. D.; Schemitsch, E. H.; Dehghan, N.
No abstract available